How to Use Cooperative Learning for Assessing Students' Emotional Competences: A Practical Example at the Tertiary Level - María Martínez Lirola (Universidad Nacional de Colombia, 2016)
Cooperative learning allows students acquisition of competences that are essential for the labour market such as leadership, critical thinking, communication, and so on. For this reason, different cooperative activities were designed in a language subject in English Studies so that students could work in groups and acquire those competences. This article describes some such activities and the emotional competences that students acquire with them. Moreover, a survey was conducted in order to establish students' opinions about the main competences they acquired with the activities designed and their opinion about a cooperative methodology. Students' answers were positive and they were aware of what they had learned.